2005
DOI: 10.1063/1.2104689
|View full text |Cite
|
Sign up to set email alerts
|

Instability and transition of flow past two tandem circular cylinders

Abstract: The instability and transition of flow past two circular cylinders arranged in tandem are investigated numerically. A steady symmetric flow is realized at small Reynolds numbers, but the flow becomes unstable above a critical Reynolds number and makes a transition to an oscillatory flow. We obtained the symmetric flow numerically and analyze its stability by applying linear stability theory. The nonlinear oscillatory flow arising from the instability is obtained not only by numerical simulation but also by dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
53
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 20 publications
9
53
0
Order By: Relevance
“…Performing a series of experiments by incrementing ⌫ in steps of 0.1, such a hysteretic mode exchange is observed for 4.6ഛ⌫ഛ5.0. Note that this range of ⌫ is shifted in our experiment in comparison to the values observed in the numerical analysis 11 where it takes place for 3.05Ͻ⌫Ͻ3.4. The finite size of the cylinders is certainly at the origin of this discrepancy between the experiment and the 2D simulation.…”
Section: -mentioning
confidence: 54%
See 3 more Smart Citations
“…Performing a series of experiments by incrementing ⌫ in steps of 0.1, such a hysteretic mode exchange is observed for 4.6ഛ⌫ഛ5.0. Note that this range of ⌫ is shifted in our experiment in comparison to the values observed in the numerical analysis 11 where it takes place for 3.05Ͻ⌫Ͻ3.4. The finite size of the cylinders is certainly at the origin of this discrepancy between the experiment and the 2D simulation.…”
Section: -mentioning
confidence: 54%
“…These modes correspond to the modes that were computed in the numerical study of Mizushima and Suehiro. 11 The transition between the slow and fast vortex shedding mode is abrupt. The values of Re that this occurs at depends on ⌫.…”
Section: -mentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] Several analytic and numerical studies have been conducted to study the characteristics of Newtonian as well as non-Newtonian fluid flows. [4][5][6] Also numerous experimental and numerical studies have been carried out for the flow past inline circular cylinders; some representative works are those of Zdravkovich, 7 Williamson, 8 Mizushima and Suehiro, 9 Sumner et al, 10 and Lam et al 11 These researchers found that the gap spacing between cylinders play an important role because it strongly affects the flow patterns and also flow induced forces.…”
Section: Introductionmentioning
confidence: 99%